2015
DOI: 10.21608/aeji.2015.17822
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Serum Hepatocyte Growth Factor Level in Diagnosis of Hepatocellular Carcinoma

Abstract: Background and study aim : Hepatocellular carcinoma (HCC) is the most common primary hepatic tumor and one of the most common cancers worldwide. New serum tumor markers are required for diagnosis of HCC as alpha-fetoprotein (AFP), which is the most widely used marker, has poor diagnostic accuracy. Hepatocyte growth factor (HGF) initially identified and molecularly cloned as a potent mitogen of primary cultured hepatocytes, has multiple activities in a variety of tissues during the course of development and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…High AFP levels have been found in 60‐70% of patients with HCC which are usually <100 ng/mL; in addition, there are other causes of increased AFP levels, such as cirrhosis. Elevated AFP was detected in 10‐33% of patients with chronic liver disease without HCC representing a risk factor for HCC development, thus suggesting that increased AFP production in these patients might reflect abnormal or altered liver cell regeneration …”
Section: Discussionmentioning
confidence: 99%
“…High AFP levels have been found in 60‐70% of patients with HCC which are usually <100 ng/mL; in addition, there are other causes of increased AFP levels, such as cirrhosis. Elevated AFP was detected in 10‐33% of patients with chronic liver disease without HCC representing a risk factor for HCC development, thus suggesting that increased AFP production in these patients might reflect abnormal or altered liver cell regeneration …”
Section: Discussionmentioning
confidence: 99%
“…[32] found that the serum HGF level was significantly higher in patients with HCC than in patients with chronic viral hepatitis or cirrhosis. Another Egyptian study found significantly high serum levels of HGF in patients with HCC than in patients with liver cirrhosis [33].…”
Section: Discussionmentioning
confidence: 99%